The effects of ground granulated blast-furnace slag blending with fly ash and activator content on the workability and strength properties of geopolymer concrete cured at ambient temperature - Deb, Partha Sarathi; Nath, Pradip; Sarker, Prabir Kumar (Materials in engineering, 2014)
•GGBFS was added in fly ash geopolymer concrete (GPC) to enable ambient curing.•Strength increased with the increase of GGBFS and reduction of activating liquid.•Heat-cured and ambient-cured GPC were compared with water-cured OPC concrete.•Tensile strengths given by codes are similar for ambient-cured GPC and OPC concrete.•The predictions are more conservative for heat-cured GPC than for ambient-cured GPC. Inclusion of ground granulated blast-furnace slag (GGBFS) with class F fly-ash can have a significant effect on the setting and strength development of geopolymer binders when cured in ambient temperature. This paper evaluates the effect of different proportions of GGBFS and activator content on the workability and strength properties of fly ash based geopolymer concrete. In this study, GGBFS was added as 0%, 10% and 20% of the total binder with variable activator content (40% and 35%) and sodium silicate to sodium hydroxide ratio (1.5–2.5). Significant increase in strength and some decrease in the workability were observed in geopolymer concretes with higher GGBFS and lower sodium silicate to sodium hydroxide ratio in the mixtures. Similar to OPC concrete, development of tensile strength correlated well with the compressive strength of ambient-cured geopolymer concrete. The predictions of tensile strength from compressive strength of ambient-cured geopolymer concrete using the ACI 318 and AS 3600 codes tend to be similar to that for OPC concrete. The predictions are more conservative for heat-cured geopolymer concrete than for ambient-cured geopolymer concrete.